Five Year Plan Assam Distirict and Subdivisional Series Kamrup - Government of Assam (Government of Assam, 1955)
The Five-Year Plan for Assam with a specific focus on Kamrup District represents a comprehensive effort to promote balanced socio-economic development through coordinated planning and targeted investment across key sectors. Designed as part of the broader state development framework, the plan aims to address regional disparities by implementing schemes that directly benefit local communities within the district and its subdivisions, including Gauhati and Barpeta. The plan outlines development initiatives across five major categories: general state plan schemes, community development projects, local development works, and special schemes implemented under constitutional provisions such as Article 275 to support tribal regions. During the plan period, Kamrup District received a total financial provision of approximately Rs. 298.41 lakhs, of which Rs. 109.01 lakhs were expended during the initial three years. Major allocations were directed toward general state plans, along with targeted investments in community development, tribal welfare initiatives, and infrastructure improvements. Agricultural development constitutes a central component of the plan, with initiatives focusing on the productive utilization of tea garden lands, expansion of minor irrigation schemes, and improved seed and fertilizer distribution systems aimed at enhancing agricultural productivity and rural livelihoods. The plan also prioritizes improvements in rural water supply systems, expansion of educational institutions, and special educational initiatives designed to increase access for tribal and disadvantaged communities. Public health programs form another key focus, with vaccination campaigns and healthcare service improvements aimed at strengthening disease prevention and community health outcomes. Administrative implementation is carried out through Subdivisional Development Committees led by local administrative authorities and supported by representatives from public organizations and community bodies, ensuring effective coordination and grassroots participation. These committees also contribute to the planning of future development programs. Overall, the plan demonstrates a structured and participatory approach to regional development, emphasizing infrastructure improvement, agricultural growth, social welfare, and community engagement to foster sustainable economic progress and improved living standards within Kamrup District.
Department of Planning and Development Government of Assam
Department of Planning and Development Government of Assam
Keywords: Assam Five-Year Plan; Kamrup District Development; Community Development Projects; Agricultural Development Programs; Minor Irrigation Schemes; Rural Water Supply; Educational Development Initiatives; Public Health Programs; Infrastructure Development; Tribal Welfare Schemes; Subdivisional Development Committees; Local Development Works